RESEARCH ON VARIABLE GRADIENT THIN-WALLED ENERGY ABSORBING COMPONENT OF SCOUR-PROOF HYDRAULIC SUPPORT - WANG ChunHua; JIANG HongXing; NIU HuiChao; AN Da (Jixie qiangdu)
For the impact of underground pressure,the roadway support equipment has poor anti-shock capability and is vulnerable to impact failure. A variable gradient thin-walled cylinder energy-absorbing and anti-shock component for anti-shock bracket is proposed. Design of different wall thickness difference and number of segments of variable gradient thin-walled cylinder energy absorbing members,The impact-crushing experiment of each parameter variable-gradient thin-walled circular tube was carried out,and the relevant energy-absorbing and anti-shock performance parameters were analyzed. The results show that the increase of the number of segments and the difference in thickness of the thin-walled circular pipe members will reduce the initial wall thickness of the thin-walled pipe,and reduce the initial peak force. Under the same average wall thickness,the average supporting reaction force and total energy absorption of the variable gradient thin-walled tubes with different wall thickness differences and number of segments are higher than ordinary thin-walled tubes by 9. 3% ～ 178%. In the variable-thickness thinwalled circular tubes with different parameters,the initial peak force,the absorbed energy,the average supporting force and the supporting force fluctuation performance parameters of the variable-gradient thin-walled circular tube members with four sections and thickness difference of 0. 5 mm are superior,which is ZQ3300 anti-shock bracket ideal anti-shock energy absorbing member,The design of the variable-gradient thin-walled circular pipe member can change the position and quantity of the plastic hinge formed by the ordinary thin-walled circular pipe member,so that the deformation of the thin-walled member tends to be more stable in the diamond mode and the mixed mode,and the energy absorption and anti-shock ability is improved.